AN ANALYSIS OF RESPONSES TO PERSONAL PROBLEMS ADOPTED BY FEMALE AND MALE STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITAS BENGKULU - Afriyani Susanti (JOALL (Journal of Applied Linguistics and Literature), 2016)
The objectives of this study were two folds; first; to find out English expressions used by male and female students of the  English Study  Program in responding to personal problems; second; to identify whether male and female students responses to personal problems were similar or different.The subjects were English Study Program at the Faculty of Teacher Training and Education of Bengkulu  University.  The total numbers of subjects were ten persons; five male and five female. Data were collected by audio-recording natural conversations informal situations outside the classroom. The results show that there were differences and similarities in responding to personal problems between male and female.